Transformational Leadership Practices in Community School - Adhikari, Surya Prasad (Tribhuvan University Journal, 2019)
This paper aimed to explore the practice of educational transformational leadership practice in community schools. To complete this study, I used qualitative research design. I selected one head teacher as a key informant applying purposive sampling procedure. In addition to the head teacher, I collected data from student, parent, chairperson, ex-chairperson, educationist, ward chairperson, and legal person from the local body from audit report for the triangulation of data. I collected the data through the audio recording. I tried to make different “themes” from the data which is related to my research objective. Transformational leadership practices as a follower and the leader in community school is found collaborative and empowering own self and other too. As follower, the respondent was responsible to her parents, parents of students, management committee and head teacher. She was influenced by elder brother in her family and by school leader at school. As a transformational leadership, the roles and responsibilities were completed in time given by the authority. The school leader has given different authority and responsibility to the followers by providing position. Those followers have actively participated to complete their roles and support to the school leader. Management committee support and agree to the school leader basically focusing on meeting visionary agendas. Likewise, students, parents and community people also supported to the school leader's vision and mission. Student outcome and school effectiveness were also satisfactory by the school concern people.